2018
DOI: 10.5206/eei.v28i2.7765
|View full text |Cite
|
Sign up to set email alerts
|

Community Schools: New Perspectives on the Wraparound Approach

Abstract: An increasing number of children and youth have mental health disorders. To address this issue, federal and provincial mental health policymakers in Canada have recommended: (a) improving the coordination of services, and (b) increasing the role that schools play in providing supports. One way to operationalize these recommendations is to implement the wraparound approach in the context of a full-service community school. This qualitative, multiple-case study of three community schools in Manitoba, Canada, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Fallon and Mueller (2017) considered wraparound as part of an ecological system, emphasising that efficacy increased when culturally responsive integration extended across components. Bartlett and Freeze (2018) found that the community school model aligned well with the principles of wraparound, and Charlton et al (2018) suggested that an integrated system of positive behavioural interventions and support, response to intervention, and Tier 3 wraparound was a model that offered many benefits. Kern et al (2017) cited evidence that having a mental health centre integrated into the school increased the efficiency of wraparound by increasing accessibility to essential services.…”
Section: Program Model Efficacy and Leadershipmentioning
confidence: 95%
See 3 more Smart Citations
“…Fallon and Mueller (2017) considered wraparound as part of an ecological system, emphasising that efficacy increased when culturally responsive integration extended across components. Bartlett and Freeze (2018) found that the community school model aligned well with the principles of wraparound, and Charlton et al (2018) suggested that an integrated system of positive behavioural interventions and support, response to intervention, and Tier 3 wraparound was a model that offered many benefits. Kern et al (2017) cited evidence that having a mental health centre integrated into the school increased the efficiency of wraparound by increasing accessibility to essential services.…”
Section: Program Model Efficacy and Leadershipmentioning
confidence: 95%
“…One of the most frequently cited barriers to wraparound success was the low competency of the facilitator or case manager (Anderson et al, 2010;Bartlett & Freeze, 2018;Maximoff et al, 2017). Other studies indicated there was a lack of commitment of adult stakeholders (Anderson et al, 2010) or a school culture that did not reflect a child-centred and strength-based philosophy (Anderson et al, 2010;Maximoff et al, 2017).…”
Section: Stakeholders' Perceptions Of Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, our model also emphasises the importance of balancing confidentiality against safeguarding and CYP's autonomy, especially in school-based services. Schools are often seen as ideal places for mental health services [10,[40][41][42] because they are accessible, closely connected to the community, and relevant staff have daily contact with, and are likely to be trusted by, CYP. Moreover, as non-medical sites, they may be less stigmatising.…”
Section: Novel Findingsmentioning
confidence: 99%